VALUATION OF THE FINANCIAL EFFECTS OF TAX ON THE EXIT OF CURRENCIES IN THE IMPORTING INDUSTRIAL SECTOR OF THE CITY OF RIOBAMBA - Puente Riofrío, Mariana Isabel; Armijo Solano, Kevin Giancarlo; Arias González, Iván Patricio (mktDESCUBRE; Vol 1 No 2 (2020): Special Edition 3rd International Scientific Congress of Administrative and Financial Sciences FADE 2019, 2020)
The taxes payment for the State is of vital importance, because through these it generates resources for the general budget of the state, in this context the tax on foreign exchange has been created with the purpose of protecting the Ecuadorian economy from the flight of capital, the present research seeks to determine the proper use of tax on foreign exchange for the industrial import sector of Riobamba, with the purpose of optimizing business resources. Through the observation, document review, data collection, verification and analysis of the corporate composition of the industries involved in the study, a financial diagnosis was made that allowed defining the current situation of each industry, as well as executing a comparative analysis of the use of the payment of the tax on the exit of foreign currency either as tax credit, expense or tax refund request to evidence the effects that product on the liquidity and profitability of the company. With the results obtained it is demonstrated that using this tax as a tax credit is the best option that the taxpayer has.